PENGARUH ANTARA KOMPETENSI PROFESIONAL GURU DAN PENGGUNAAN LEMBAR KERJA SISWA (LKS) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN ADMINISTRASI UMUM JURUSAN ADMINISTRASI PERKANTORAN DI SMK SWASTA JAMBI MEDAN T.P 2019/2020 - Dosma Aderia Pardede (Jurnal Administrasi dan Perkantoran Modern, 2021)
The purpose of this study was to determine the effect of teacher professional competence and the use of student worksheets (LKS) on student learning outcomes in general administration subjects majoring in office administration at SMK Swata Jambi Medan T.P 2019/2020.This type of research is the Facto Exposure research. The population in the study was all students of class X-AP Vocational School Private Jambi Jambi, amounting to 76 students. The sample in this study was the total number of total sampling population of 76 students. Data collection techniques used were observation, documentation, and questionnaires. Validity test for questionnaire item analysis uses the product moment formula, and the reliability is obtained using the Cronbach alpha formula. The data analysis technique used in this research is multiple linear regression test and to prove the truth of the hypothesis used the t test, f test, and the determinant test (R ^ 2).Based on the results of data analysis using SPSS 20 software application assistance, obtained by multiple linear regression equation y = 23,992 + 0,476X1 + 0,283X2 then the teacher professional competency variable (X_1) has a positive and partially significant effect on student learning outcomes (Y) with value of t_count>t_table (7.648> 1.666). While the use of worksheets (X_2) also has a positive and significant effect on student learning outcomes with a value of tcount of 3.152 and ttable 1.666. Together the teacher's professional competence and the use of worksheets have a positive and significant effect on student learning outcomes with the value f_count>f_table(103,428> 3.12). The percentage contribution of the influence of teacher professional competence and the use of student worksheets on student learning outcomes is 86%.